Assessment of Ionizing Radiation Induced Dicentric Chromosome and Micronuclei in Human Peripheral Blood Lymphocytes for Preliminary Reconstruction of Cytogenetic Biodosimetry - M. Syaifudin; Y. Lusiyanti; S. Purnami; Y.S Lee; C.M. Kang (PPIKSN-BATAN, 2017)
Cytological biodosimetry methodology has been widely used for determining and estimating the precise irradiation dose received by victims in the situation of emergency irradiation exposure. The aim of this study was to assess the gamma-ray induced dicentric chromosomes and micronuclei (MN) in peripheral blood lymphocytes for preliminary reconstruction of cytogenetic biodosimetry. The study was performed by exposing blood samples taken from seven healthy donors to gamma rays at dose range of 0.1 to 4.0 Gy, followed by culturing them for 48-72 hours at 37 °C by the standard technique. After being harvested, the chromosome spread at metaphase and MN were stained with Giemsa's solution. The results showed that the frequency of both dicentrics and MN of samples were increased with the increase of radiation dose. Considerable increases of both cytologic damages were found in the samples exposed to higher doses (>2 Gy). Significant differences (p>0.05) only found in mean frequencies of MN for all doses tested. Reconstruction of the relationship of these frequencies with doses was found to follow linear-quadratic curve lines and was consistent with that of other studies. Due to the aforementioned advantages namely the dependence of radiation dose and dose rate on the frequency of of both dicentric and MN, despite some limitations, these assays have been found to be suitable to be used as biological dosimetry. It is concluded that in order for this cytogenetic biodosimety method by means of scoring/assessing the radiation-induced dicentrics and MN could be used in radiation emergency and protection, and further studies with larger numbers of samples need to be done.Received: 12 November 2015; Revised: 18 Mei 2016; Accepted: 08 December 2016